TINJUAN YURIDIS MENGENAI PENERAPAN CONCURSUS (KETENTUAN PASAL 65 KUHP) OLEH HAKIM DALAM HUKUM PIDANA INDONESIA (Studi Putusan Nomor 91/Pid. B/2013/Pn. AMP). - Dedi Supriadi (Yayasan Akrab Pekanbaru, 2019)
The legal problems in Indonesia are very complex, especially those relating to judicial decisions in court, both decisions with a single criminal offense or combined criminal acts (concurrent) or concursus from several cases that have occurred often we find irregularities in a court decision that is not appropriate with what is expected by justice seekers. The provisions regarding perbarengan (concursus) are basically a provision regarding how to settle cases and impose criminal penalties. In the case where one person has committed more than one criminal offense in which all the criminal acts have not been examined and decided by the court. Concretely, the provisions for the regulation regulate and determine whether to hear or examine (solve) the case and the method or system of imprisonment against one person who has committed more than one criminal offense, all of which have not been examined and decided by the court. The results showed that the application of concursus provisions in Article 65 of the Indonesian Criminal Code in Indonesian criminal law can provide a sense of justice and therefore the application of concursus provisions in Article 65 of the KUHP realist concursus to be implemented and applied by judges in deciding criminal acts of prosecution and punishment systems to avoid the omission of criminal acts criminal offense committed by the defendant.